1917 Cal. Stat. 221, § 5 - (:unkn) unknown (General Publisher, 1917)
Prohibited the use, or intent to use unlawfully against another, carrying, or possessing a dagger, dirk, dangerous knife, razor, stiletto, loaded pistol, revolver, other firearm, or any instrument or weapon commonly known as a blackjack, slung-shot, billy, sandclub, sandbag, metal knuckles, bomb, or bombshell, or any other dangerous or deadly instrument or weapon. Violators guilty of a felony. Carrying or possessing these weapons while committing, attempting, or threatening to commit a felony, breach of the peace, or any act of violence against the person or property of another shall be presumptive evidence of carrying or possessng with intent to use in violation of this section.
--
Keywords: CARRY - INTENT TO COMMIT CRIME